Ketentuan Umum Pajak Dan Retribusi Daerah Terhadap Pengenaan Retribusi Parkir - Ni Putu Reina Mahargita; I Ketut Kasta Arya Wijaya; Luh Putu Suryani (Jurnal Preferensi Hukum, 2025)
Taxes are very important in raising funds for the state, which ultimately leads to national development and improving individual welfare. Regional Retribution is a payment made to the Regional Government by an individual or company in return for services or permits that meet their needs. As for the formulation of the problems raised, namely 1) How is the legal arrangement of parking levy imposition based on Indonesian legislation? 2) What are the juridical reasons for the imposition of parking fees based on Denpasar Mayor Regulation Number 35 of 2021? The research method used is normative legal research. The results show that various laws and regulations regulate local taxes and levies, but the only regulations that specifically regulate parking fees are Denpasar City Regional Regulation Number 19 of 2011 and Denpasar Mayor Regulation Number 35 of 2021. New regulations are needed to clarify that parking services on public roads require payment. Local Regulation No. 35 regulates the collection of public street retribution and states that the clarity of the collection is determined by the Local Government in accordance with applicable laws and regulations.